The impact of educational mismatch on firm productivity: Evidence from linked panel data - Stephan Kampelmann; François Rycx (Institute for the Study of Labor (IZA), 2012)
We provide first evidence regarding the direct impact of educational mismatch on firm productivity. To do so, we rely on representative linked employer-employee panel data for Belgium covering the period 1999-2006. Controlling for simultaneity issues, time-invariant unobserved workplace characteristics, cohort effects and dynamics in the adjustment process of productivity, we find that: i) a higher level of required education exerts a significantly positive influence on firm productivity, ii) additional years of over-education (both among young and older workers) are beneficial for firm productivity, and iii) additional years of under-education (among young workers) are detrimental for firm productivity.
Keywords: I21; J24; 330; educational mismatch; productivity; linked panel data; GMM; Unterbeschäftigung; Qualifikation; Matching; Arbeitsnachfrage; Produktivität; Schätzung; Belgien